Penggunaan Multimedia Interaktif untuk Meningkatkan Hasil Belajar Siswa Materi Bilangan Bulat di Sekolah Dasar - Artika, Fitri; Yusuf, M. (Jurnal Nispatti, 2025)
Online learning at SDN 102094 of Paya Pinang cannot facilitate student’s learning needs. The result of the AKM simulation conducted in September 2021 were 87,5% of students with score bellows 70. The students had difficulty solving problems related to numeracy. Therefore, the use of interactive multimedia in learning began to be used. This study was conducted to measure students learning outcomes after using interactive mathematics multimedia. The result showed that in first cycle as many as 68,75% of students obtained mastery learning and increase in second cycle, was 93,75% of students completed arithmetic operation on integers. Based on the result of second cycle, it can be concluded that the use of interactive multimedia can improve student learning outcomes in the matter of counting integer operations in class VISDN 102094 Paya Pinang.